The Relationship Between Learning Activities and the Ability to Understand Natural Science Concepts in Class V - Muharlida, Aprilia; Marhayani, Dina Anika; Sumarli, Sumarli (CV. Rayyan Dwi Bharata, 2024)
This research aims to: 1) Describe the relationship between student learning activities and understanding of science concepts in the material of changes in the shape of objects. The research used is correlation or relationship research with a quantitative approach. The population in this study were all 5th grade students at SDN 14 Kuala Selakau with a total of 26 students. The sampling technique used was the saturated sampling technique. Saturated sampling technique is a sample determination technique when all members of the population are used as samples. Data were analyzed univariately with a significance level of 5% (0.05). For hypothesis testing, a prerequisite test was used, namely the normality test using the Chi square formula. The results of the research show that: 1) There is a relationship between learning activities and students' understanding of science concepts in the material on changes in the shape of point objects with the criteria for the strength of the relationship being in the very strong category with a correlation coefficient of 0.98. Understanding students' concepts provides a coefficient of 97.81% for student learning activities and the remaining 2.19% is influenced by other factors. Thus, it can be concluded that if the student's learning activities are good, the higher the student's understanding of science concepts, or conversely, the lower the student's learning activities, the lower the student's understanding of science concepts.